The theory of protection - Corden, W. M. (Oxford : Clarendon Press, 1971)
The key chapters in this book are Chapter 3, which sets out the theory of effective protection in partial equilibrium terms, and Chapters 4 and 5, which similarly develop the theory of tariff structure in general equilibrium terms
Includes index.
Includes bibliographical references: p. 253-258.
osc 12/07/2018
Loans
Keywords: Protectionism